Bureaucratizing the Atlantic Revolution:: The "Saskatchewan Mafia" in the New Brunswick Civil Service, 1960-1970 - Pasolli, Lisa (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
Abstract Louis J. Robichaud recognized at the time of his election as premier in 1960 that bureaucratic modernization was urgently needed to translate the political gains of the "Atlantic Revolution" into workable social and economic programs in New Brunswick. To provide leadership in civil service reform, Robichaud recruited seven ex-Saskatchewan Co-operative Commonwealth Federation bureaucrats who became known as the "Saskatchewan Mafia." This article uses their experiences to explore the bureaucratization of the Atlantic Revolution, and argues that this group played a crucial role in the transformation of New Brunswick’s political bureaucracy and thus in the modernization of the province as a whole.